2021
DOI: 10.3390/healthcare9030253
|View full text |Cite
|
Sign up to set email alerts
|

Work Engagement in Nurses during the Covid-19 Pandemic: A Cross-Sectional Study

Abstract: In some areas of Spain, health services and professionals working in the front line against the Sars-Cov-2 virus have been widely overwhelmed at all levels. Therefore, the objective of this study was to assess the level of work engagement of Spanish nurses during the COVID-19 pandemic. A cross-sectional study was carried out. The sample consisted of 510 active nurses from all over Spain, without age exclusion, who voluntarily accepted to participate in the study. Work engagement was assessed with the 9-item Ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 32 publications
7
37
1
Order By: Relevance
“…Our study results are thus in line with the German study by Wildgruber et al who found that the work engagement of nurses decreases with increasing pandemic-related stress [ 13 ]. In addition, there is overlap with international study findings by Allande-Cussó et al [ 69 ] who identified high work engagement among Spanish nurses, as well as with the study by Zhang et al [ 44 ], who found low stress and high work engagement among Chinese nurses during the COVID-19 pandemic. The latter study also found a negative correlation between pandemic-related stress and work engagement.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our study results are thus in line with the German study by Wildgruber et al who found that the work engagement of nurses decreases with increasing pandemic-related stress [ 13 ]. In addition, there is overlap with international study findings by Allande-Cussó et al [ 69 ] who identified high work engagement among Spanish nurses, as well as with the study by Zhang et al [ 44 ], who found low stress and high work engagement among Chinese nurses during the COVID-19 pandemic. The latter study also found a negative correlation between pandemic-related stress and work engagement.…”
Section: Discussionmentioning
confidence: 79%
“…A high level of work engagement was found among the majority of the outpatient nurses. The fact that nurses’ work engagement is high despite all the challenges of the pandemic has also been found in studies from the national and international context [ 13 , 62 , 69 ]. In this context, Giménez-Espert et al concluded that nurses’ work engagement may be even higher than ever before due to the extreme circumstances of the COVID-19 pandemic, which could be due to their high resilience and awareness of the enormous importance of their work [ 62 ].…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, the present study may provide insight on the mediating role of work engagement as a mediator in the interaction between EI and work outcomes on behalf of such a health-care workforce humankind reposes the utmost faith on a quotidian reliance on [ 40 ]. According to the derivative evidence [ 25 ], the obtained findings reported in the current article have yielded significant associations for the direct interaction between EI and work performance crosswise to the mediating role of work engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with the research of Gómez-Salgado (2021) because the excessive service burden during the COVID-19 pandemic will affect the motivational factor according to Herzberg's theory which has an impact on work absenteeism. (Gómez-Salgado et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between work engagement and extended working time among nurses; In other words, an excessive service load during the COVID-19 pandemic will affect mental health and decreased work engagement. However, working overtime voluntarily, motivated by personal development and fulfillment, promotes increased work engagement (Gómez-Salgado et al, 2021).…”
Section: Relationship Between Nurse Motivation and Job Engagementmentioning
confidence: 99%